A Study on Parametric S-metric Spaces - Das, Abhishikta; Bag, T. (Communications in Mathematics and Applications, 2022)
In this paper, some topological properties are discussed and some results on completeness, totally boundedness, compactness on parametric S-metric spaces are developed.